Effects of risk perception, SNS uses, personal characteristics on climate change participation behaviors of millennials in South Korea - Yeon-A Son; Jong Woo Jun (Cogent Business & Management, 2024)
Global climate change has also become a problem faced by college students in Korea. College students can also participate in climate change-related actions, such as reducing disposables. This study investigated the effects of perception of climate change risk, media use, and personal characteristics on participation behavior for climate change with university students, who are practical stakeholders in climate change. Hypothesis 1 is susceptibility, Hypothesis 2 is severity perception, Hypothesis 3 is SNS use, Hypothesis 4 is self-efficacy, and Hypothesis 5 is the effect of social conformity on participation behavior. Data was collected through a survey, and as a result of data analysis, it was found that the social susceptibility among the two risk susceptibility increased participation behavior. It was found that personal susceptibility did not affect participation behavior. Next, the perception of the severity of climate change was verified as a key factor in increasing climate change participation behavior. Perception of severity was the most influential variable in the regression analysis. People who use SNS information on climate change were also active in participation. Among personal characteristics, people with high self-efficacy had positive participation behavior, but people's social conformity did not affect participation behavior. These results show the perception of climate change from the perspective of college students, the millennial generation, and provide practical implications for climate change participation behavior.
Keywords: 650; Climate change; risk perception; severity perception; SNS uses; self-efficacy; and social conformity